Pengembangan bahan ajar Teori dan Apresiasi Sastra berbasis literasi budaya - Anshari Anshari; Sakaria Sakaria (Seminar Nasional LP2M UNM, 2019)
Development of Teaching Materials and Literature Appreciation Based on Cultural Literacy. This study aims to describe the feasibility and effectiveness of theoretical teaching materials and the appreciation of cultural literacy-based literature. Teaching materials were developed using the 4-D model in the Indonesian Language Education Study Program in the Postgraduate Program of Makassar State University. The results of the study show that the teaching materials developed have been appropriate and effective to be used in theories and literary appreciation. Teaching materials are feasible because they fulfill the feasibility aspects, namely the feasibility of content, the feasibility of presentation, and the feasibility of language. Teaching materials are effectively used because there are significant differences in student learning outcomes before using and after using instructional materials.